2009
DOI: 10.1063/1.3208058
|View full text |Cite|
|
Sign up to set email alerts
|

Fractal character of titania nanoparticles formed by laser ablation

Abstract: Titania nanoparticles were fabricated by laser ablation of polycrystalline rutile in water at room temperature. The resulting nanoparticles were analyzed with x-ray diffraction, Raman spectroscopy, and transmission electron microscopy. The electron micrograph image of deposited nanoparticles demonstrates fractal properties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
0
8
0
Order By: Relevance
“…Distilled or deionized water is the most frequently employed liquid medium for synthesizing NMs via LAL. Generally, during laser ablation, the dissolved oxygen or an oxidizing species from the plasma-induced decomposition of water will react with the matter from the target during laser ablation, leading to the generation of diverse oxides (e.g., Ag 2 O, ZnO, , TiO 2 , Al 2 O 3 , MgO, MnO, Mn 2 O 3 , γ-MnO 2 , Mn 3 O 4 , , Co 3 O 4 , and Cu 4 O 3 ) and hydroxides (e.g., Mg­(OH) 2 , ). In this process, the redox potentials play a dominant role in determining the degree of oxidation of the LAL-generated products.…”
Section: Material Process Liquid and Laser Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…Distilled or deionized water is the most frequently employed liquid medium for synthesizing NMs via LAL. Generally, during laser ablation, the dissolved oxygen or an oxidizing species from the plasma-induced decomposition of water will react with the matter from the target during laser ablation, leading to the generation of diverse oxides (e.g., Ag 2 O, ZnO, , TiO 2 , Al 2 O 3 , MgO, MnO, Mn 2 O 3 , γ-MnO 2 , Mn 3 O 4 , , Co 3 O 4 , and Cu 4 O 3 ) and hydroxides (e.g., Mg­(OH) 2 , ). In this process, the redox potentials play a dominant role in determining the degree of oxidation of the LAL-generated products.…”
Section: Material Process Liquid and Laser Parametersmentioning
confidence: 99%
“…For industrial applications, colloids are becoming relevant at the multiple-gram-scale, which recently became accessible by LSPC. , Because the processing parameters (e.g., bulk target, solvent and solutes, and system temperature and pressure) and laser parameters (e.g., wavelength, pulse duration, pulse energy, repetition rate, and number of laser pulses) can be flexibly adjusted, a library of NMs covering nearly the entire periodic table can be produced . In addition to the crystalline spheres that are usually generated, soluble, reactive, or supersaturated seed concentrations during LSPC may lead to the formation of nonspherical NMs through ripening, and the resulting morphologies include fractal, hexagonal, flower-like, , football-like, fullerene-like, leaf-like, nanocube, nanowire, nanospindle, , nanoribbon, hollow, core–shell, necklace, nanotruffle, nanosheet, tubular, and nanodisk . These features of LSPC have recently stimulated product commercialization by start-ups on at least three continents, including Particular GmbH in Germany and in-house spin-offs at IMRA in the USA and Hamamatsu Nanotechnology in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…6,7 This technique, known as pulsed laser deposition (PLD), has been used in various environments (liquids, high gas pressures) and with different laser pulses characteristics (pulse length, wavelength, fluence, polarization). Fractal aggregates obtained from thousands of ns pulses have been demonstrated in water 8 and at high argon pressure . 9,10 When the laser pulse duration is reduced to less than a picosecond, PLD enters in the femtosecond regime (fs-PLD), and a different physical mechanism for ablation sets in.…”
Section: Introductionmentioning
confidence: 99%
“…Here we analyze experimental data of Titanium dioxide (TiO 2 ) nanostructures obtained by fs-PLD in air at ambient conditions on different substrates. TiO 2 is a strategic material in many technologically important areas, such as heterogeneous catalysis, 8,14,15 photo-assisted oxidation, 16 optical 17 and photovoltaic 18 devices. Under the same experimental conditions (laser fluence, pulse duration, polarization, distance of the target from the substrate, see Methods) we found that different nanostructures are formed on different substrates, ranging from single nanoparticles on graphite, ramified fractals on silicon and long fractal chains on quartz.…”
Section: Introductionmentioning
confidence: 99%
“…Fractal structures have been obtained on various substrates, by deposition of the target material during ablation in air (Celardo et al 2017), in supercritical fluids (Saitow et al 2012) and even in water (Musaev et al 2009). However, pieces of evidence that this sort of structures exist also in the pristine ablation solution are limited to a report on the structure of silver nanoparticles synthesized in water by fs-PLAL, and also in such a case, the emphasis was on the structure deposited on solid surfaces (Santillán et al 2015).…”
Section: Introductionmentioning
confidence: 99%